146 Functional Priorities in High Cervical Spinal Cord Injury: Implications for Upper Limb Nerve Transfer Surgery. (April 2023) - Javeed, Saad; Greenberg, Jacob K.; Zhang, Justin; Dibble, Christopher; Khalifeh, Jawad M.; Wilson, Thomas J.; Zager, Eric L.; Faraji, Amir H.; Mahan, Mark Alexander; Midha, Rajiv; Burks, Shelby; Levi, Allan D.; et al.
Abstract : INTRODUCTION: High cervical spinal cord injury (SCI) results in complete impairment in upper limb function. Nerve transfer is an innovative reinnervation strategy for upper limb reanimation following SCI. However, the impact of upper limb motor recovery on the degree of long-term functional outcomes remains unknown. METHODS: A prospective cohort of high cervical SCI (C1-C4) patients enrolled in SCI model systems (SCIMS) was included. Baseline neurological examinations and functional independence measures (FIM) in eating, bladder-function, and transfers (bed/wheelchair/chair) were evaluated. At one-year follow-up, functional independence was compared in patients who gained recovery (motor grade >=3) in C5-elbow flexion, C6-wrist extension, C7-elbow extension, and C8-finger flexion. A multivariable logistic regression evaluated the impact of motor recovery on functional independence on composite outcome of feeding, bladder-function, and transfers. RESULTS: Between 1992-2016, 405 high cervical SCI patients were included. At baseline, 97% patients had impaired upper limb function with inability in all functions. At one-year follow-up, the largest proportion of patients gaining independence in eating, bladder-function, and transfers had recovery in C8-finger-flexion and C6-wrist-extension. C5-elbow-flexion recovery had lowest translation into functional independence. Patients who achieved C7-elbow-extension were able to transfer independently. On multivariable analysis, C8-finger-flexion recovery had 12-times higher odds (p=0.004) and C6-wrist-extension recovery had 7-times higher odds (p=0.04) of gaining functional independence in composite outcome. Age >=60 years and motor complete SCI (ASIA-A-B) were associated with reduced odds of gaining independence. 8% patients improved ASIA grades from baseline to 1-year. CONCLUSIONS: Following cervical SCI, C8-finger-flexion and C6-wrist-extension recovery can maximize functional independence. Recovery of C7-elbow-extension can increase transfer capability. This information may prioritize reinnervation strategies for individualized decision-making for nerve transfers in high cervical SCI.